Fungsi dan Makna Kebah pada Masyarakat Mukomuko - Hasanah, Jasmiatul; Lubis, Bustanuddin; Sarwono, Sarwit (Jurnal Korpus, 2025)
This research aims to describe the function and meaning of the kebah in the Mukomuko community. The method used in this research is a qualitative descriptive method. The results of the research found that kebah refers to a form of oral literature in the form of folklore, history or legend. The main function of the kebah is as a means of education, reflecting public awareness of the importance of education in shaping life. Kebah functions as a medium of expression, where people can express opinions and complaints without feeling embarrassed, because the identity of the character being told remains anonymous. Other functions of the kebah include upholding authority, challenging tradition, entertainment, unification, socialization, forming cultural identity, and social criticism. In terms of its meaning, kebah contains a deep message, especially regarding the relationship between parents and children. This relationship functions as a foundation for forming children's character and values, where parents act as role models in teaching morality and ethics. This meaning not only affects individuals, but also impacts the broader social structure, forming generations of mutual respect. Apart from that, kebah also emphasizes the meaning of luck, which is understood as the result of a combination of opportunities and an individual's ability to exploit them, as well as the result of hard work. Thus, kebah not only has an impact on individuals, but also has an impact on the formation of broader social structures.